Synovial tuberculosis of the hand: An ancient disease in an unusual localisation - Ramos, Renato Franz Matta; Cancian, Lucas; Calcagnotto, Fernando; Zeni, Ricardo; Varela, Gabriel; Burgues, Tamsin; Silva, Jefferson Braga (Indian Journal of Plastic Surgery, 2017)
Background: Tuberculosis is the most prevalent infectious disease in the world. It is mainly caused by Mycobacterium tuberculosis. Osteoarticular tuberculosis represents 1%–3%. Tenosynovitis is the most common form of the disease in the hand. Aims: The aim of this study is to present an update of synovial tuberculosis. Materials and Methods: The authors present a literature review, the clinical and surgical management and case reports. Results: The outcomes were satisfactory and were not report complications. Conclusions: Early diagnosis, surgical transection of the transverse carpal ligament, debridement and complete excision of the infected synovium may be required, along with antituberculosis drugs. Knowledge of this disease in the hand can provide a better diagnosis and outcome.
Keywords: Hand; joint; synovial; tuberculosis